Oxidative stress, DAMPs, and immune cells in acute pancreatitis: molecular mechanisms and therapeutic prospects - Chen, Hanwen; Wang, Yanhong; Zippi, Maddalena; Fiorino, Sirio; Hong, Wandong (Frontiers in Immunology, 2025)
Acute pancreatitis (AP) is a gastrointestinal disease characterized by inflammation of the pancreas and is associated with high rates of morbidity and mortality. The pathogenesis of AP involves a complex interplay of cellular and molecular mechanisms, including oxidative stress, damage-associated molecular patterns (DAMPs), and the infiltration of various immune cells. This review aims to provide a comprehensive overview of the molecular mechanisms underlying AP, the role of different immune cells in its progression and potential therapeutic perspectives. Oxidative stress, characterized by an imbalance between reactive oxygen species (ROS) and the antioxidant defense system, plays a crucial role in AP. ROS not only contribute to cell necrosis and apoptosis, but also activate immune cells and perpetuate inflammation. DAMPs released from damaged cells activate the innate immune response by interacting with pattern recognition receptors (PRRs), leading to the recruitment of immune cells such as neutrophils, macrophages and dendritic cells. These immune cells further amplify the inflammatory response by releasing cytokines and chemokines. Neutrophils are among the first responders in AP, contributing to both tissue damage and repair, as well as the double-site sword effect of neutrophil extracellular traps (NETs). Other immune cells, including T cells, dendritic cells, mast cells and monocytes/macrophages, are involved in modulating the inflammatory response and tissue repair processes. The balance between pro- and anti-inflammatory immune responses is critical in determining the severity and outcome of AP. A table of targeted drugs or substances available in clinical trials is provided at the end of this paper, with the aim of providing available opportunities for clinical treatment. Nevertheless, precise targeted drugs are still urgently needed in clinical treatment, where more in-depth research is needed.